2005
DOI: 10.1039/b510026g
|View full text |Cite
|
Sign up to set email alerts
|

Alkyne coupling at a rhenium–monocarborane substrate: synthesis of Re,B-η2:σ-butadienyl complexes

Abstract: Treatment of 7-NH(2)Bu(t)-nido-7-CB(10)H(12) in tetrahydrofuran (THF) with LiBu(n)(3 equiv) and then [ReBr(CO)(3)(THF)(2)] gives the rhenacarborane dianion [1-NHBu(t)-2,2,2-(CO)(3)-closo-2,1-ReCB(10)H(10)](2-), isolated as the bis-[N(PPh(3))(2)](+) salt (4). Iodine oxidation of this Re(I) intermediate gives the Re(III) complex [1,2-mu-NHBu(t)-2,2,2-(CO)(3)-closo-2,1-ReCB(10)H(10)] 6 in which the carborane functions formally as an 8-electron (6pi+ 2sigma) donor. Reaction of with ligands L in the presence of Me(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…An X-ray diffraction study confirmed that in this iodo derivative there are two intramolecular amino bridges between cage vertices and the molybdenum [38]. Interestingly, on reaction with PEt 3 in refluxing thf a CO molecule in 39 is substituted by the phosphine, rather than an amino bridge being lifted, with formation of an {MoI(CO) 2 (PEt 3 )} group.…”
Section: Molybdenum and Tungsten Compoundssupporting
confidence: 53%
See 2 more Smart Citations
“…An X-ray diffraction study confirmed that in this iodo derivative there are two intramolecular amino bridges between cage vertices and the molybdenum [38]. Interestingly, on reaction with PEt 3 in refluxing thf a CO molecule in 39 is substituted by the phosphine, rather than an amino bridge being lifted, with formation of an {MoI(CO) 2 (PEt 3 )} group.…”
Section: Molybdenum and Tungsten Compoundssupporting
confidence: 53%
“…Elimination of H 2 from G again produces a piperidinyl group bridging between a cage a-boron and the molybdenum center, as seen in H, which is the anion of 35. In contrast the reaction between [7-NHBu t -nido-7-CB 10 [38]. An X-ray diffraction analysis of 36 confirmed its molecular structure.…”
Section: Molybdenum and Tungsten Compoundssupporting
confidence: 50%
See 1 more Smart Citation
“…10 The reagent has been used successfully for the decarbonylation of different Re tricarbonyl complexes. [10][11][12][13][14][15][16][17] Kurtz et al, e.g., prepared a series of compounds of the type cis-[Re(diimine)(CO) 2 (L)Cl] (where L ¼ P(OEt) 3 , PMe 3 ) by exploiting the trans-labilizing effect of phosphorus ligands to facilitate carbonyl replacement. 12,17 Similarly the group of Wilson synthesized and structurally characterized analogous complexes as the active photoactivated species in a study that reported the in vitro anticancer activity of rhenium(I) tricarbonyl complexes bearing water-soluble phosphines.…”
Section: Introductionmentioning
confidence: 99%
“…10 The reagent has been used successfully for the decarbonylation of different Re tricarbonyl complexes. [10][11][12][13][14][15][16][17] Kurtz et al, e.g., prepared a series of compounds of the type cis-[Re(diimine)(CO) 2 (L)Cl] (where L = P(OEt) 3 , PMe 3 ) by exploiting the trans-labilizing effect of phosphorus ligands to facilitate carbonyl replacement. 12,17 Similarly the group of Wilson synthesized and structurally characterized analogous complexes as the active photoactivated species in a study that reported the in vitro anticancer activity of rhenium(I) tricarbonyl complexes bearing water-soluble phosphines.…”
Section: Introductionmentioning
confidence: 99%